A high selectivity millimeter wave filter chip with good roll‐off based on IPD technology. Issue 11 (28th July 2022) - Xu, Yao; Wu, Yongle; Yang, Yuhao; Wang, Weimin
Abstract: In this article, a high selectivity mm‐wave filter chip based on integrated passive devicies (IPD) technology is proposed. Two adjustable transmission zeros are introduced on both sides of the passband to achieve high roll‐off characteristic. The odd‐even equivalent circuits are used to analyze and calculate the S ‐parameters, and the procedure to design a filter is given. Finally, two filter chips with different bandwidths are manufactured based on IPD technology. The measured results show that the minimum insertion losses of the two chips are 1.82 and 1.39 dB, respectively, and their return losses are better than 15 dB. In addition, their roll‐off and stopband suppression are of high level, and the chip sizes are only about 2.8 × 2 mm 2 .